Prognostic Significance of Circulating Immune Subset Counts in Nasopharyngeal Carcinoma - Xie H; Zhang L; Chen L; Zhou W; Zhang L; Su Y; Li B; Ding P; Xiao Y; Lu T; Gong X; Li J (ImmunoTargets and Therapy)
Honghui Xie,1– 3,* Lin Zhang,1,3,4,* Lizhi Chen,5,* Wenchao Zhou,1,6 Lijuan Zhang,1,3 Yong Su,1– 3 Bocheng Li,1,6 Peng Ding,1,6 Yun Xiao,1– 3 Tianzhu Lu,1,2,4,7 Xiaochang Gong,1,2,4,7 Jingao Li1,2,4,7 1NHC Key Laboratory of Personalized Diagnosis and Treatment of Nasopharyngeal Carcinoma, Jiangxi Cancer Hospital, Nanchang, Jiangxi, 330029, People’s Republic of China; 2Department of Radiation Oncology, Jiangxi Cancer Hospital, Nanchang, Jiangxi, 330029, People’s Republic of China; 3Jiangxi Clinical Research Center for Cancer, Jiangxi Cancer Hospital & Institute, The Second Affiliated Hospital of Nanchang Medical College, Nanchang, Jiangxi, 330029, People’s Republic of China; 4JXHC Key Laboratory of Tumour Metastasis, Jiangxi Cancer Hospital, Nanchang, Jiangxi, 330029, People’s Republic of China; 5Department of Oncology, Shangrao People’s Hospital, Shangrao, Jiangxi, 334000, People’s Republic of China; 6Jiangxi Medical College, Nanchang University, Nanchang, Jiangxi, 330064, People’s Republic of China; 7JXHC Key Laboratory of Tumor Microenvironment and Immunoregulation, Jiangxi Cancer Hospital, Nanchang, Jiangxi, 330029, People’s Republic of China*These authors contributed equally to this workCorrespondence: Xiaochang Gong, NHC Key Laboratory of Personalized Diagnosis and Treatment of Nasopharyngeal Carcinoma, Jiangxi Cancer Hospital, No. 519, Beijing East Road, Nanchang, Jiangxi, 330029, People’s Republic of China, Email gxcanddw@163.com Jingao Li, NHC Key Laboratory of Personalized Diagnosis and Treatment of Nasopharyngeal Carcinoma, Jiangxi Cancer Hospital, No. 519, Beijing East Road, Nanchang, Jiangxi, 330029, People’s Republic of China, Email lijingao@hotmail.comPurpose: This study aimed to assess the prognostic value of circulating immune cells in newly diagnosed, non-metastatic nasopharyngeal carcinoma (NPC) and to develop a nomogram combining immune cell counts with clinical characteristics.Methods: In this retrospective study, patients with non-metastatic NPC treated between January 2015 and December 2018 were included. Circulating immune cell subtypes were measured using cellular immunochip technology. Survival outcomes were assessed using Kaplan–Meier analysis, and independent prognostic factors were identified through multivariate analysis (MVA). A prognostic nomogram was constructed and evaluated using Harrell’s concordance index (C-index).Results: A total of 459 patients were included, with a median follow-up of 62 months. Optimal cutoff values for CD4+ T cells (420 cells/μL), CD8+ T cells (430 cells/μL), CD3+ T cells (1100 cells/μL), and CD4/CD8 ratio (1.00) were determined using X-tile. Higher levels of CD4+ T cells (78.6% vs 64.2%, p < 0.001), CD8+ T cells (77.5% vs 71.4%, p = 0.113), CD3+ T cells (83.1% vs 70.0%, p = 0.003), and CD4/CD8 ratio (77.6% vs 60.0%, p = 0.001) were associated with better 5-year progression-free survival. MVA confirmed high CD4/CD8 ratio and CD3+ T cell count as independent prognostic factors. The nomogram combining CD3+ T cells, CD4/CD8 ratio, and N classification showed superior prognostic accuracy compared with the clinical model alone (C-index: 0.686 vs 0.648, p < 0.001).Conclusion: Circulating immune cells, particularly CD3+ T cells and CD4/CD8 ratio, are significant prognostic indicators in NPC. The proposed nomogram may help predict disease progression and support individualized treatment planning.Keywords: immune cells, nasopharyngeal carcinoma, nomogram, progression-free survival